Fake News Law Enforcement Efforts During the Campaign Period - Hartanto; Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the despicable acts that can be done online is spreading fake news (fraud). In the midst of a Scam campaign, the point is to make open conclusions, lead assumptions, form assertions, and have fun testing the insights and rigor of web and social media clients. Cases of fraud in the middle of the campaign period often occur and spread so quickly because of the variables that are easily accepted by society. In order for data dissemination to be effective by word of mouth spreading through online media very quickly, this research was conducted in the city of Yogyakarta